Unity in Action: The Mapalus Model as a Blueprint for Rural Economic Empowerment - Fajar Wuryaningrat, Nikolas; Kumajas, Lydia I.; Mandagi, Deske W. (International Journal of Sustainable Business, Management and Accounting, 2025)
Background of study: Circular economy has been widely studied in manufacturing industries, yet its application in rural agricultural communities remains underexplored. Most derivative product developments often overlook whether they meet the real needs of local communities. Aims and scope of paper: This paper aims to introduce the Mapalus Circular Economic Model, which integrates the traditional Minahasan concept of mapalus—a cooperative system based on kinship—into rural economic empowerment. The scope focuses on exploring how agricultural derivative products can be developed and consumed within rural communities to create a sustainable local economy. Methods: The study employs a literature review method, synthesizing existing research on circular economy, community-based development, and the role of mapalus in strengthening collaboration, knowledge transfer, and social cohesion. Result: : Findings highlight that the Mapalus Circular Economic Model positions rural communities as both producers and consumers of derivative agricultural products. This dual role fosters sustainable economic cycles, enhances community self-reliance, and supports environmental preservation. The integration of local traditions, knowledge resources, policies, and external collaborations is identified as essential for successful implementation. Conclusion: The Mapalus Model represents a blueprint for rural economic empowerment through circular economy practices grounded in cultural values. By revitalizing mapalus traditions, the model fosters collective action, reduces poverty, and strengthens social bonds. However, as this study is based on literature review, empirical validation through field research is required to ensure its practical applicability and effectiveness in real-world settings.